2011
DOI: 10.1016/s1413-8670(11)70135-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pneumococcal serotypes and resistance to antimicrobial agents in patients with meningitis: ten-year analysis

Abstract: Resistance to penicillin and ceftriaxone was detected in 23.6% and 12.5% of the strains, respectively, and predominated in children aged two years or less and during the 2005-2009 period. There were 24 different serotypes of pneumococcus and 79.8% of the serotypes were represented in the 7-valent conjugated vaccine [PVC7].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The prevalence of penicillin resistance seems to be variable, with reported rates as low as 0% [53] , [54] , [55] and as high as 27.9% [25] , [54] in Brazil. It is important to point out that previously published rates used the 2008 CLSI breakpoints to determine β-lactams susceptibility, and in this study, penicillin MICs ≥4 µg/mL were not observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of penicillin resistance seems to be variable, with reported rates as low as 0% [53] , [54] , [55] and as high as 27.9% [25] , [54] in Brazil. It is important to point out that previously published rates used the 2008 CLSI breakpoints to determine β-lactams susceptibility, and in this study, penicillin MICs ≥4 µg/mL were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that previously published rates used the 2008 CLSI breakpoints to determine β-lactams susceptibility, and in this study, penicillin MICs ≥4 µg/mL were not observed. Non-susceptibility is mostly associated with serotypes 14, 19F, 23F, 6B and 19A [24] , [25] , [54] in Brazil. Although Zemlicková et al (2005) [24] demonstrated a heterogeneous pre-vaccination population of penicillin-resistant pneumococci, Barroso et al (2012) [25] suggested a major role of clone Spain 9V -3 among pneumococci with this resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of S.pneumoniae with reduced susceptibility to penicillin has been observed in Brazil [ 5 ] and in many parts of the world. In addition, reduced susceptibility to extended-spectrum cephalosporins such as ceftriaxone has become a serious problem because it limits the available treatment options for pneumococcal invasive diseases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significant increases in the penicillin-resistance rates of invasive pneumococcal strains have been reported in Brazil. 16 Pneumococcal infections, which may be seen in every age group, may result in severe sequel or death due to treatment failures caused by bacterial resistance, especially if they occur in life-threatening locations. Thus, knowledge on pneumococcal resistance patterns enables initiation of an appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%